Isolation of an ovine pulmonary surfactant-associated anionic peptide bactericidal for Pasteurella haemolytica. - Brogden, K A (1996)
Ovine pulmonary surfactant is bactericidal for Pasteurella haemolytica when surfactant and bacteria mixtures are incubated with normal ovine serum. To isolate this component, surfactant (1 mg/ml) was centrifuged at 100,000 x gav, and the supernatant was fractionated by HPLC. Fractions were eluted with acetonitrile (10-100%)/0.1% trifluoracetic acid and tested for bactericidal activity. Amino acid and sequence analysis of three bactericidal fractions showed that fraction 2 contained H-GDDDDDD-OH, fraction 3 contained H-DDDDDDD-OH, and fraction 6 contained H-GADDDDD-OH. Peptides in 0.14 M NaCl/10 microM ZnCl2 (zinc saline solution) induced killing of P. haemolytica and other bacteria comparable to defensins and beta-defensins [minimal bactericidal concentration (MBC)50 range, 0.01-0.06 mM] but not in 0.14 M NaCl/10 mM sodium phosphate buffer, pH 7.2/0.5 mM CaCl2/0.15 mM MgCl2 (MBC50 range, 2.8-11.5 mM). Bactericidal activity resided in the core aspartate hexapeptide homopolymeric region, and MBC50 values of aspartate dipeptide-to-heptapeptide homopolymers were inversely proportional to the number of aspartate residues in the peptide. P. haemolytica incubated with H-DDDDDD-OH in zinc saline solution was killed within 30 min. Ultrastructurally, cells contained flocculated intracellular constituents. In contrast to cationic defensins and beta-defensins, surfactant-associated anionic peptides are smaller in size, opposite in charge, and are bactericidal in zinc saline solution. They are members of another class of peptide antibiotics containing aspartate, which when present in pulmonary secretions may help clear bacteria as a part of the innate pulmonary defense system.